1997
DOI: 10.1063/1.120179
|View full text |Cite
|
Sign up to set email alerts
|

Charge carrier mobility in poly(p-phenylenevinylene) studied by the time-of-flight technique

Abstract: The charge carrier transport in poly(p-phenylenevinylene) (PPV) is investigated by the time-of-flight technique. Mobilities of positive carriers in PPV are determined and the dispersive character of transport is established. The dispersion parameters are analyzed in the frame of a multiple trapping model. The drift mobility of the positive carriers is in the range of 10-5 cm2/V at room temperature for an electric field of 105 V/cm and increases with increasing field and temperature. The mobility shows thermall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
72
1
1

Year Published

1998
1998
2012
2012

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 162 publications
(79 citation statements)
references
References 14 publications
5
72
1
1
Order By: Relevance
“…There are very few experimental results on unsubstituted PPV. A time-of-flight study by Lebedev et al 37 on unsubstituted PPV showed an Arrhenius temperature dependence, ln μ ∝ T −1 , of the mobility, while we exhibit a temperature dependence somewhere in between the Arrhenius dependence and the Bässler dependence (Eq. (9)) depending on the reorganization energy.…”
Section: Discussionmentioning
confidence: 99%
“…There are very few experimental results on unsubstituted PPV. A time-of-flight study by Lebedev et al 37 on unsubstituted PPV showed an Arrhenius temperature dependence, ln μ ∝ T −1 , of the mobility, while we exhibit a temperature dependence somewhere in between the Arrhenius dependence and the Bässler dependence (Eq. (9)) depending on the reorganization energy.…”
Section: Discussionmentioning
confidence: 99%
“…This is much higher than that measured for structurally well ordered conjugated polymers, where a of 52 meV was reported, but comparable to some molecularly doped polymer systems ͑typically in the region of 80-100 meV͒ 14 and more disordered conjugated materials, such as PPV. 20 An important parameter in the understanding of charge transport is the temperature dependence of the mobility and its effect on the shape and the scale of the photocurrent transients. The influence of temperature on the transients is shown in Fig.…”
Section: A Mobility Measurementsmentioning
confidence: 99%
“…Transient studies of hole transport in conjugated polymers [2][3][4][5] have established that the hole mobility is well described by…”
mentioning
confidence: 99%